2016
DOI: 10.1103/physrevc.93.044614
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for chemical fractionation of radioactive xenon precursors in fission chains

Abstract: Mass-spectrometric analyses of Xe released from acid-treated U ore reveal that apparent Xe fission yields significantly deviate from the normal values. The anomalous Xe structure is attributed to chemically fractionated fission (CFF), previously observed only in materials experienced neutron bursts. The least retentive CFF-Xe isotopes, 136 Xe and 134 Xe, typically escape in 2:1 proportion. Xe retained in the sample is complimentarily depleted in these isotopes. This nucleochemical process allows understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…However, this composition was derived from statistical correlations and its presence has never been observed in any terrestrial or extraterrestrial material. Recently, Meshik et al 15. proposed an alternative explanation to U-Xe for the origin of atmospheric Xe.…”
mentioning
confidence: 99%
“…However, this composition was derived from statistical correlations and its presence has never been observed in any terrestrial or extraterrestrial material. Recently, Meshik et al 15. proposed an alternative explanation to U-Xe for the origin of atmospheric Xe.…”
mentioning
confidence: 99%
“…This interpretation implies that phase Q is of solar, rather than of presolar origin (Meshik et al. ). Processes involved in the origin of Q‐Xe have been investigated by plasma experiments dedicated to study the adsorption of Xe onto organics defects (Marrocchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative view considers Q as being locally derived from an initial nebula mix now represented by the solar composition. It has been demonstrated that~2% of Xe-H apparently present in phase Q may not be necessarily originated from stellar nucleosythesis (Meshik et al 2016), but could result from the addition of xenon originating from chemically fractionated fission (CFF) of 244 Pu, which was extant during the formation of phase Q. This nucleo-chemical process typically yields 136 Xe to 134 Xe in 2:1 proportion, with little 132 Xe and 131 Xe, and no lighter isotopes, which are shielded from fission by stable isobars.…”
Section: Origin Of Chondritic Noble Gases and Their Evolution During mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that alternative models have been proposed regarding the origin of U-Xe. The primary terrestrial atmosphere has been proposed to have been enriched in 134 Xe and 136 Xe due to ejection of these isotopes from plutonium/uranium-rich lithologies during fission of the now-extinct 244 Pu [chemical fractionation fission process ( 10 )]. A giant impact event, such as the one proposed to have formed the Moon, could then have induced major loss of this primary atmosphere, leaving a remaining Xe component that was complimentarily depleted in 134 Xe and 136 Xe isotopes.…”
Section: Introductionmentioning
confidence: 99%